Sinopsis en Idioma Inglés - Reflexión Política, Revista (Reflexión Política, 2000)
Resumen POLITICAL REFORM: IN THEORY AND IN PRACTICE ALFONSO GÓMEZ GÓMEZ This article exposes the necessity to reform institutions that in these times are the source or focal point of corruption. For many years now, theoretical statements and the expression of distressed sentiments in the face of this scourge have not been formulated into any concrete solutions. In fact, some of the drawn up methods have had inane results in view of the magnitude of the problem that Colombian people face, giving the State a concerning and disturbing classification in the international arena. It is urgent to establish a supposition law, according to which the State owns the patrimonial increases from public officials and allies which aren’t based on legal means consented to by the Law.